Nonmyeloablative Allogeneic Stem-Cell Transplantation for Metastatic Renal Cell Cancer: A Review and Update - P. Erotocritou; H. Ahmed; S.S. Patel; I. Shergill; H.R. Patel; P.M. Shah; M. Arya (The Scientific World Journal)
Metastatic renal cell carcinoma (RCC) is resistant to conventional chemotherapy and radiotherapy. However, immunotherapy appears to be effective in 15—20% of cases, with interleukin-2 becoming the standard therapy for this disease. As a consequence of the immune susceptibility of RCC, other avenues of immunotherapy are being explored, such as nonmyeloablative allogeneic stem cell transplantation (NST). A number of trials have shown NST to be effective in varying degrees, causing partial or complete regression. Although nonmyeloablative conditioning is safer than myeloablative conditioning, its role has yet to be clearly proven as many studies have shown variable effect. Alongside this limitation, transplant-related toxicity also forms obstacles. Regardless of the limitation of NST, further refinement of the technique, with appropriate patient selection, may lead to this being an effective therapeutic choice for a significant number of individuals.